UPAYA PENGAMALAN NILAI-NILAI MORAL AGAMA DI SENTRA BALOK PADA ANAK USIA DINI KELOMPOK B USIA 5-6 TAHUN DI RAUDHATUL ATHFAL NURUL HUDA KABUPATEN MALANG - Liyatus Zahroh; Khoirul Asfiyak; Ika Anggraheni (UNISMA, 2020)
The purpose of this study is to describe the planning of religious moral values habituation, the implementation of religious moral values habituation, monitoring and evaluation of religious moral values habituation in group b children (ages 5-6 years) in Raudhatul Athfal Nurul Huda Malang. The method used by researchers is to use a qualitative approach. The location in this study is in RA Nurul Huda which is located on Jl. Mosque no.28 Langlang Singosari District Malang Regency East Java Province 65151. The conclusion of this study is the Planning of religious moral values in group b children (ages 5-6 years) in RA Nurul Huda Malang there are several points, namely: Arranging the Vision and Mission , Procedures, and work programs. From this point, school planning is mature enough in the formation of moral values in children. Implementation of religious moral values in group b children (ages 5-6 years) at RA Nurul Huda Malang, which is: habituation, assessment process, data management, and reporting. These four points are carried out to shape the moral values of religion in children in RA Nurul Huda. Monitoring and Evaluation of religious moral values in group b children (ages 5-6 years) in RA Hurul Huda Malang there are 2 monitoring and evaluation carried out, namely: Learning and Monitoring itself. Learning includes several evaluations, namely: Daily, weekly, monthly, semester, and semester reporting.